Respuestas

  • Usuario de Brainly
2013-04-18T08:11:24+02:00

4.............10.................1

------- + ---------- = ---------------

(2x-3)...(4x²-9)........(2x+3)

 

4.............10................................1

------- + ------------------ = ---------------

(2x-3)...(2x-3)(2x+3)........(2x+3)

 

 

(2x + 3)4   + 10.........................1

----------------------------- = ---------------

(2x-3)(2x+3).........................(2x+3)

 

8x + 12 + 10........................1

------------------------- = -------------

(2x - 3)(2x+3).................(2x + 3)

 

(8x + 22) (2x + 3)

----------------------- = 1.........simplifico

(2x - 3)(2x + 3)

 

8x + 22

------------- = 1

(2x - 3)

 

8x  + 22 = 2x - 3

8x - 2x = - 3 - 22

6x = - 25

x = - 25 /6

 

espero que te sirva, salu2!!!!